Vaccination in the Era of Precision Medicine: Tailoring Immunization Strategies for Individual Risk Profiles - Shruti Morankar; Samruddhi Waghchaure (International Journal of Vaccines, 2024)
The introduction of precision medicine has caused a paradigm change in the vaccine landscape. Conventionally, vaccination programmes have been homogeneous, targeting immunity at the population level without taking into consideration the individual differences in immune response and vulnerability to diseases that can be prevented by vaccination. However, a more individualised approach to immunisation has been made possible by current developments in genetics, immunology, and data analytics. Within the context of precision medicine, the idea of adjusting vaccination regimens to each patient's unique risk profile is examined in this article. The implementation of precision vaccination has several hurdles, including ethical considerations, privacy concerns, and the requirement for a strong infrastructure to facilitate data integration and analysis. Inequalities in vaccine uptake and effectiveness may also be made worse by differences in access to healthcare and genetic testing. Collaboration amongst various stakeholders, such as healthcare professionals, researchers, policymakers, and technology developers, is necessary to tackle these difficulties. the era of precision medicine presents previously unheard-of chances to completely transform immunisation programmes. We may advance towards a future where vaccinations are not only effective at the population level but also customised to meet the specific needs of each individual, maximising the impact of vaccination efforts on public health, by adopting a personalised approach to immunisation
Keywords: Genetics; Precision medicine; homogeneous; immunisation; paradigm; vaccination